2017
DOI: 10.15376/biores.12.3.5749-5774
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Extraction from Coconut Shell Using Aprotic Ionic Liquids

Abstract: Coconut shell, a natural biopolymer, is available in high amounts as waste in many countries. It could potentially be a crucial renewable source of raw materials for the carbon fiber industry. In this study, a series of aprotic ionic liquids, [Bmim] Cl. The recyclability of the ionic liquids during the dissolution process (up to four times) was also scrutinized. The structure and properties of the untreated coconut shell and regenerated lignin were characterized by Fourier transform infra-red (FTIR) spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Ionic liquids (and ionic liquid-based mixtures) have been extensively studied for their application in pretreatments for the deconstruction and fractionation of lignocellulosic biomass [136][137][138]. Most cases are based on the selective dissolution of cellulose [139][140][141][142][143] or lignin [144][145][146][147], but attempts to dissolve the whole lignocellulosic biomass have been carried out as well [148][149][150][151]. Nevertheless, in most cases, a solid residue was left at the end of the dissolution experiment and even the studies that reported complete dissolution of biomass stated that their solutions were hazy and non-uniform [152].…”
Section: Pretreatment Of Lignocellulosic Biomass For Hemicellulose Vamentioning
confidence: 99%
“…Ionic liquids (and ionic liquid-based mixtures) have been extensively studied for their application in pretreatments for the deconstruction and fractionation of lignocellulosic biomass [136][137][138]. Most cases are based on the selective dissolution of cellulose [139][140][141][142][143] or lignin [144][145][146][147], but attempts to dissolve the whole lignocellulosic biomass have been carried out as well [148][149][150][151]. Nevertheless, in most cases, a solid residue was left at the end of the dissolution experiment and even the studies that reported complete dissolution of biomass stated that their solutions were hazy and non-uniform [152].…”
Section: Pretreatment Of Lignocellulosic Biomass For Hemicellulose Vamentioning
confidence: 99%
“…For example, the inherent recalcitrance of biomass requires an initial pretreatment step to render polysaccharides free from lignin for subsequent enzymatic or chemical hydrolysis into fermentable sugars. To solubilize lignocellulosic biomass, certain hydrophilic ILs are highly effective and environmentally friendly pretreatment agents that generate relatively low amounts of biomass-derived inhibitors compared with other conventional pretreatment methods [[46], [47], [48]].…”
Section: Environmental Stresses In Biorefinerymentioning
confidence: 99%
“…Although the complete dissolution of the whole biomass has been tested [137,138], the selective dissolution of its components has been more frequently proposed. Several ILs have demonstrated their effectiveness for lignin dissolution [139], but imidazolium-based ILs appear as the most representative examples [140][141][142][143][144][145][146][147][148][149]. As lignin can be selectively extracted from lignocellulosic biomass by employment of ILs, new simpler pretreatment methods can be developed for lignin isolation and purification [150,151].…”
Section: Properties Kraft Lignin Lignosulfonate Soda Ligninmentioning
confidence: 99%